Freedom in a Time of Climate Catastrophe - Song, Robert (Studies in Christian ethics, 2026)
The failure of Western publics to respond congruently to the scale of the climate catastrophe should be understood as a lack of freedom. This article describes four ways in which collective agency is likely to be exercised in the coming decades in relation to the climate crisis: climate governance, reactionary populism, green authoritarianism, and pluriform localism. The prospect that these may fail to achieve climate goals within the necessary time horizon raises the question of the meaning of freedom if the window of opportunity for adequate climate action is closing. Drawing on Walter Benjamin's theological and materialist conception of messianic time in the face of the loss of the future, we can delineate a Christian account of freedom indexed to participation in the cross and resurrection of Christ.